151 A CROSS-SECTIONAL EXPLORATION OF INTERPROFESSIONAL COLLABORATION WITHIN INTEGRATED CARE TEAMS OPERATING UNDER THE NATIONAL INTEGRATED CARE PROGRAMME FOR OLDER PERSONS. (25th October 2022) - O'Donnell, D; Whitty, H; Devaney, C; Ahern, E; Radomska, A; Harnett, PJ
Abstract: Background: There is an evidence and practice gap in understanding the knowledge, skills, and behaviours required of Health Care Professionals (HCPs) for effective interprofessional collaboration in the context of integrated care for older people. Furthermore, little is known about the outcome factors that may be associated with effective interprofessional collaboration among HCPs working in integrated care teams for older people. Methods: A cross-sectional representative survey of HCPs employed in the 30 integrated care teams (ICTs) operating under the National Integrated Care Programme for Older Persons was undertaken. The survey measured indicators of competence identified in a previously co-designed framework for core competencies for interprofessional collaboration within ICTs for older people. Results: The study explores an association between competencies in interprofessional collaboration among HCPs employed in ICTs for older persons and factors associated with higher job satisfaction including psychological safety, trust, and work engagement. Findings elaborate on instances of service innovation which resulted from interprofessional collaboration within the team. Conclusion: The study findings provide a baseline understanding of competencies for interprofessional collaboration within the ICTs operating in the NICPOP. This will support an implementation evaluation of the co-designed framework that will generate realist evidence regarding how ICTs for older people foster, enhance and sustain their proficiency in interprofessional collaboration. This realist evaluation will identify new models of interprofessional team working and explore the outcomes that are associated with interprofessional collaboration from the perspective of older people, their family carers, and HCPs who are working as part of an interprofessional team.